Fungibility, labels and consumption - Johannes Abeler; Felix Marklein (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
Fungibility of money is a central assumption in the theory of consumer choice: any unit of money is substitutable for another. This implies that the composition of income or wealth is irrelevant for consumption. We find in a field experiment that even in a simple, incentivized setup many subjects do not treat money as fungible. When a label is attached to a part of their budget, subjects change consumption according to the label. A controlled laboratory experiment confirms this result and further shows that subjects with lower cognitive abilities are more likely to violate fungibility. The findings lend support to behavioral models of narrow bracketing and mental accounting. One implication of our results is that in-kind benefits distort consumption more strongly than usually assumed.
Keywords: C91; C93; D01; H31; I38; 330; fungibility; in-kind benefits; mental accounting; narrow bracketing; field experiment; laboratory experiment; Geld; Kognition; Konsumentenverhalten; Verhaltensökonomik; Test; Sachtransfer; Feldforschung; Theorie; Deutschland